Physical Disability and Increased Loneliness among Married Older Adults: The Role of Changing Social Relations - Warner, David F. (Soc Ment Health, 2015)
Examining the social context of disablement, we investigated how changes in social relations affect loneliness among married older men and women. With longitudinal data on 914 married persons from the National Social Life, Health, and Aging Project (NSHAP), we found that changes in the quality of marital and nonmarital relations moderate the effect of disability on loneliness in unexpected ways. Increases in negative marital quality buffer the effect of physical disability, while increases in nonmarital support exacerbate it. Although not predicted by existing theory, these findings are consistent with some prior work suggesting that health-related stressors, like physical disability, condition the meaning of changes in social relations. We find, however, that negative social relations ameliorate loneliness only among disabled married men; disabled married women experience increased loneliness under similar circumstances. These differences have not been previously identified. We conclude by discussing the gendered nature of the social context of disablement.